HUBUNGAN TINGKAT STRESS DENGAN DERAJAT DISMENORE PRIMER PADA MAHASISWI PROGRAM STUDI SARJANA KEDOKTERAN FAKULTAS KEDOKTERAN UNIVERSITAS UDAYANA - Nurharta, Desak Made Pratista Sari Mahadevi; Wahyuni, Nila; Dinata, I Made Krisna (Universitas Udayana, 2024)
Background: Primary dysmenorrhea is pain or tenderness during menstruation without any gynecological abnormalities. The main contributory cause to primary dysmenorrhea is an increase in prostaglandin production, one of which can be brought on by stress. Stress is the response of the human body to stressors and can be a defense system of the human body. It has been determined from numerous research that stress is relatively common among medical students. The stress experienced by female students can cause disturbances in the endocrine system so that it can be a trigger or a factor in aggravating the degree of dysmenorrhea. Objective: This study aims to determine the relationship between stress levels and the degree of primary dysmenorrhea in students of the Medical Undergraduate Study Program, Faculty of Medicine, Udayana University. Methods: This study used an observational analytic research study with a cross sectional design. By using total sampling, 81 students from the Medical Education Study Program at the Faculty of Medicine at Udayana University, year 2020, were selected as the research sample. Data on stress were obtained from filling out the PSS-10 questionnaire and data on primary dysmenorrhea were obtained from the NRS. Analysis of research data using chi-square test to determine the correlation between stress and primary dysmenorrhea. Results: The results of the study showed that there was no relationship between stress and primary dysmenorrhea with a p-value of 0,79. Conclusion: The conclusion of this study is that there is no significant relationship between stress levels and the degree of primary dysmenorrhea in students of the Medical Undergraduate Study Program, Faculty of Medicine, Udayana University. Keywords : Stress, stress level, dysmenorrhea, primary dysmenorrhea